2016
DOI: 10.1038/npjpcrm.2016.51
|View full text |Cite
|
Sign up to set email alerts
|

Patient coping strategies in COPD across disease severity and quality of life: a qualitative study

Abstract: Quality of life (QoL) has a weak relationship with lung function (LF) impairment in COPD; some cope well despite poor LF, whereas others suffer disproportionate QoL impairment despite well-preserved LF. Adjuvant non-pharmacological interventions such as rehabilitation and psychological/behavioural support may help if acceptable and targeted appropriately, but they are under-used and sometimes declined by patients. This study aimed to explore and understand variations in experiences and coping strategies in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
5
45
0
2
Order By: Relevance
“… 6 Psychological and behavioral factors may influence individual perceptions of symptom severity, and strategies used by patients to cope with the burden of symptoms and disability are still incompletely understood. 7 Several studies 1 , 10 , 13 have conducted surveys pairing patients with the doctors taking care of them and have observed differences in the way the disease is perceived. However, a limiting factor is that different questionnaires have been used for the two groups.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Psychological and behavioral factors may influence individual perceptions of symptom severity, and strategies used by patients to cope with the burden of symptoms and disability are still incompletely understood. 7 Several studies 1 , 10 , 13 have conducted surveys pairing patients with the doctors taking care of them and have observed differences in the way the disease is perceived. However, a limiting factor is that different questionnaires have been used for the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been echoed more recently in qualitative studies of patients' experiences of living with COPD by Marx et al 48 and Brien et al 49 Drawing out the implications for health care, Marx et al 48 concluded that patients may benefit from the early integration of palliative care in care systems, to help them to understand and accept their life situation and enhance their reduced quality of life. The authors argued that the multidisciplinary nature of palliative care, including psychological support and volunteer work, may help to address patients' psychosocial needs.…”
Section: Patients' Experiences Of Chronic Obstructive Pulmonary Diseamentioning
confidence: 97%
“…The authors argued that the multidisciplinary nature of palliative care, including psychological support and volunteer work, may help to address patients' psychosocial needs. Brien et al 49 examined experiences of COPD in patients with varying quality of life. Most patients used multiple coping strategies, yet over half reported significant challenges coping with COPD.…”
Section: Patients' Experiences Of Chronic Obstructive Pulmonary Diseamentioning
confidence: 99%
“…Indeed, acceptance of the disease is associated with behaviour change [26]. Furthermore, acceptance of the diagnoses and limitations, having a realistic disease understanding and developing a rational response to the disease are ways of enabling taking control [69]. Another considerable outcome is emotional intelligence, i.e.…”
Section: Example 2: Patients' Social Networkmentioning
confidence: 99%